1997
DOI: 10.1007/bf02113586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary tract infection during outpatient follow-up after renal transplantation

Abstract: Seven hundred and twenty-seven renal transplant patients are reviewed with respect to the occurrence of urinary tract infection (UTI) after renal transplantation. UTI was defined as the detection of both bacteriuria (10(5) CFU/ml) and pyuria (10 leukocytes/hpf). UTI developed in 11 of the inpatients (20.8%) and in 30 (4.2%) of the outpatients during a one-year period. Among outpatients, 12 had symptomatic infections, comprising seven with acute pyelonephritis and five with acute cystitis. Asymptomatic UTI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
4
32
2
1
Order By: Relevance
“…Renal grafts are particularly susceptible to the direct and/or indirect consequences of UTI. There is greater risk of bacterial invasion of the transplanted kidney, because of the immunosuppression and vulnerability of the graft that follow surgical manipulation (3)(4)(5). Intraoperative ureteral stents and bladder catheter may also increase the risk of UTIs in transplanted patients (5,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal grafts are particularly susceptible to the direct and/or indirect consequences of UTI. There is greater risk of bacterial invasion of the transplanted kidney, because of the immunosuppression and vulnerability of the graft that follow surgical manipulation (3)(4)(5). Intraoperative ureteral stents and bladder catheter may also increase the risk of UTIs in transplanted patients (5,12).…”
Section: Discussionmentioning
confidence: 99%
“…These infections are thought to be directly attributable to exposure to pathogens during the early postoperative period and to immunosuppressive therapy (3)(4)(5). The improvement of surgical procedures, rapid removal of the urethral catheter, and antibiotic prophylaxis have reduced the incidence of UTI during the immediate postoperative period (6,7), but it is still higher in transplanted patients than in the normal population.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infection (UTI) in kidney transplant recipients is directly attributable to pathogen exposure during the early postoperative period and to immunosuppressive therapy (Rubin and Tolkoff-Rubin 1991;Goya et al 1997;Schmaldienst and Horl 1998). Although improved surgical procedures, rapid urethral catheter removal, and antibiotic prophylaxis have reduced the incidence of UTI during the immediate postoperative period (Sagalowsky et al 1983;Rabkin et al 1998), the use of more potent immunosuppressive drugs to reduce the incidence of rejection predisposes kidney transplant recipients to increased risks of UTI (de Souza and Olsburgh 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Lower and upper urinary tract infections are related to bacterial exposure, surgical procedure, previous asymptomatic bacteriuria, and immunosuppressive therapy. 5,6 The effect of posttransplant pyelonephritis on the kidney allograft's long-term function and survival remains controversial. Abbott and associates have shown that urinary tract infection occurring late after a kidney transplant is associated with increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%